The Role of Gemcitabine in the Treatment of Cholangiocarcinoma and Gallbladder Cancer: A Systematic Review - Brian H Dingle; R Bryan Rumble; Melissa C Brouwers (Canadian Journal of Gastroenterology)
BACKGROUND: Cholangiocarcinoma and gallbladder cancer are difficult to treat curatively. The treatment of choice is surgery, dependent on detection at a resectable stage. No chemotherapy or radiotherapy options have shown substantial activity. Gemcitabine has demonstrated response in similar cancers. Considering the lack of treatment options for cholangiocarcinoma and gallbladder cancer, a systematic review of the evidence on gemcitabine use for these indications was performed.